Losing oneself (in a good way): On the value of full attention - Debus, Dorothea (European Journal of Philosophy, 2015)
The present paper considers the question whether, and if so how, a subject's full attention to an object which she interacts with might have value. More specifically, I defend the claim that in order for a subject's activity to have value, it is sufficient that the subject give her full attention to the object towards which the activity is directed.
CRIS-Team Scopus Importer:2024-10-02